Cannabis Use and Dependence among French Schizophrenic Inpatients - Lejoyeux, Michel; Basquin, Anne; Koch, Marie; Embouazza, Houcine; Chalvin, Florence; Ilongo, Michaelle (Frontiers in Psychiatry, 2014)
Background: To assess the prevalence of cannabis use and dependence in a population of schizophrenic inpatients and to compare schizophrenics with and without cannabis consumption. Methods: One hundred one schizophrenic patients were examined during their first week of hospitalization. They answered the PANNS scale of schizophrenia, the CAGE and the Fagerström questionnaire, and the DSM-IV-TR criteria for cannabis, alcohol, opiates, and nicotine use dependence were checked. We also assessed socio-demographic characteristics, the motive of cannabis consumption, and the number of cannabis joints and alcoholic drinks taken. Results: The prevalence of cannabis consumption was 33.6% among schizophrenic inpatients. Schizophrenics consuming cannabis were younger than non-schizophrenics (33.3 vs. 44.7 years p < 0.0001), more often male (77 vs. 54%, p = 0.02) and had been hospitalized for the first time in psychiatry earlier (24.3 vs. 31.3 p = 0.003). Eighty-eight percent of cannabis consumers were dependent on cannabis. They were more often dependent on opiates (17 vs. 0%) and alcohol (32 vs. 7.4%, p = 0.001) and presented compulsive buying more often (48 vs. 27%, p = 0.04). Logistic regression revealed that factors associated to cannabis consumption among schizophrenics were cannabis dependence, male gender, pathological gambling, opiate dependence, number of joints smoked each day, and compulsive buying. Conclusion: 33.6% of the schizophrenic patients hospitalized in psychiatry consume cannabis and most of them are dependent on cannabis and alcohol. Hospitalization in psychiatry may provide an opportunity to systematically identify a dependence disorder and to offer appropriate information and treatment.